The discovery of time - Toulmin, Stephen (University of Chicago Press, 1965)
Taking the history of science full circle to look at how scientists developed their ideas about history, The Discovery of Time is a delightful and thought-provoking companion to The Architecture of Matter and The Fabric of the Heavens. Authors Stephen Toulmin and June Goodfield explore the evolution of our thinking about the past clearly and plainly, showing the interplay and conflict between natural philosophy and religious dogma that continue in classrooms today. Beginning their story in prehistoric traditions of oral history, which functioned to preserve cultural and spiritual truths, they examine the ancients' relationship with their own past as it related to their explanations for the way things had come to be. The Greeks began incorporating what we would recognize as historical elements into their contemporary writings, blending the legends of the past with their philosophical thinking. The exquisitely demonstrated expansion and contraction of the perceived past, from the infamous calculation of the date of the biblical Creation to modern ideas about the Big Bang, shake the modern reader's certainty a little--essential for any new understanding. The drama of Kant, Vico, Darwin, Lyell, and other thinkers competing for the world's attention to create the greatest change in the history of history late in the 19th century is compelling reading and closes the book on a tentative note.